SUBSIDIARY OPERATIONS IN BEAUTY INDUSTRY IN U.S.A - Mikkonen, Leo (My University, 2008)
The main goal is to analyze strategic options of subsidiary operations in beauty industry and to evaluate the probable effects of these choices in business relationships. The purpose of this study from the business perspective is for top management purposes to form an understanding of the prerequisites, motives and best alternatives for Lumene’s subsidiary operations in USA. The interdependence of the actors in subsidiary’s relationship network creates a complex and challenging environment for strategic management. Theoretical framework seeks to combine the theories of business environment analysis with the theories behind the key determinants of efficient subsidiary operations and business relationship management in order to point out the most relevant factors in subsidiary operation strategies. Expanding sales, marketing and logistical operations in the near future seems a necessary step for Lumene’s management to take. Own facilities in warehousing and production operations would require substantial growth of sales volumes. New recruitments in sales, marketing operations and logistical operations would most likely create a very positive impact to business relationships with current customers. The challenge for Lumene’s management lies in improving information management and winning new customers.
Keywords: Subsidiary Operations; Beauty Industry; Retail Industry; Supply Chain Management; Business Relationship Management; fi=Markkinointi|en=Marketing|; fi=Kansainvälisen yritystoiminnan koulutusohjelma|